Variability and Heritability of Spike Length in F1 Hybrids of Durum Wheat (Triticum Durum) - B.I. Mamaraximov; J.S. Mavlanov; U.A. Beknayev; B.S. Kushmatov; L.B. Mavlanov; E.A. Yuldashev (American Journal of Botany and Bioengineering, 2025)
The study was conducted during 2021–2023 in the rainfed fields of the Central Experimental Farm of the Scientific Research Institute of Rainfed Agriculture. The experiment involved 20 F1 hybrid combinations of durum wheat along with their parental forms. The type of inheritance for spike length was evaluated using the formula of P. Petr and K. Frey (1966). According to the results, the inheritance coefficient in F1 hybrids ranged from –12.4 to +5.2. In some combinations (Leukurum-3 × Tilling), depression was observed; in several combinations (Leukurum-3 × Plc/ruff, Leukurum-3 × Sebatel, Leukurum-3 × Icajoudy1, Marvarid × Ousloukos), positive deviation was recorded; while in other combinations (Leukurum-3 × Korifla/Aeg, Leukurum-3 × Younes, Yoqut-2014 × Joric 69, Yoqut-2014 × Atlast 1, Mrb3/Mna1 × Leukurum-3), heterosis effects were noted.